2019
DOI: 10.1016/j.ejmech.2019.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Chemoenzymatically synthesized ganglioside GM3 analogues with inhibitory effects on tumor cell growth and migration

Abstract: Ganglioside GM3, belonging to glycosphingolipid family, has been known as tumor-associated carbohydrate antigen on several types of tumor. Many studies have revealed that GM3 plays a role in cell proliferation, adhesion and differentiation, which is crucial in the process of cancer development. In the present study, we firstly synthesized novel mannose containing GM3 analogues by enzymatic hydrolysis and chemical procedures. Then the antiproliferative activity of the novel analogues along with galactose contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Together with some other analogues which were synthesized previously in our laboratory [15,16], for a series of GM3 analogues containing different sugars with α-2,6 sialosides, the structure-activity relationships were discussed. We found that both different glycosyl residues and ceramide or sphingosine moiety could influence anti-proliferation and anti-migration activities.…”
Section: Structure-activity Relationships Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with some other analogues which were synthesized previously in our laboratory [15,16], for a series of GM3 analogues containing different sugars with α-2,6 sialosides, the structure-activity relationships were discussed. We found that both different glycosyl residues and ceramide or sphingosine moiety could influence anti-proliferation and anti-migration activities.…”
Section: Structure-activity Relationships Discussionmentioning
confidence: 99%
“…From the previous studies in our laboratory, some GM3 analogues with anticancer activities have been synthesized [15,16]. In the present study, we developed methods to synthesize GM3 analogues from commercially available substrates and reagents.…”
Section: Introductionmentioning
confidence: 99%
“…Gangliosides are closely related to the proliferation, movement, migration, adhesion, apoptosis, and immune escape of cancer cells. , Various types of gangliosides are typically expressed on the surface of cancer cells, called tumor-associated carbohydrate antigens. Among these, the simplest ganglioside GM3 (NeuAca3Galb4Glcb1Cer) is closely associated with human tumors, especially malignant tumors. , The expression of GM3, which is not detected in normal melanocytes, is increased in primary and metastatic melanoma . Saha et al demonstrated that the ability of B16 mouse melanoma cells to metastasize and invade has increased, as the cell surface exhibits a high level of GM3 expression. , Some GM3 derivatives have already been found having inhibitory effects on tumor cell growth and migration in vitro . , Because of its important roles in the process of tumor development, GM3 has been validated as a promising target for cancer immunotherapy …”
Section: Introductionmentioning
confidence: 99%
“…22,23 Some GM3 derivatives have already been found having inhibitory effects on tumor cell growth and migration in vitro. 24,25 Because of its important roles in the process of tumor development, GM3 has been validated as a promising target for cancer immunotherapy. 26 Effective immunotherapy relies on the choice of the antigen, and gangliosides, especially GM3, play an important role in it.…”
Section: Introductionmentioning
confidence: 99%